Productivity and Nutritive Value of Black Soldier Fly (Hermetia illucens) Larvae Fed with Different Waste Substrates - Barrera, Janet; Salinas, Erwin R.; Rivera, Algie R.; Malalis, Juneven S.; Bagaforo, Engr. Roger O.; Araya, Junas P.; Sulay, Dr. Darwin Lloyd D. (Future Science / FSH-PH Publications, 2023)
Due to the unavailability and rising market price of fishmeal and soybean meal, insect larvae, such as black soldier fly larvae (BSFL: Hermetia illucens), are currently being investigated as an alternate source of protein for swine and poultry. The productivity and nutritional value of BSFL were examined in this study together with the effects of various waste substrates. There were two experimental containers for every treatment and were replicated three times and laid out using a Completely Randomized Design (CRD). A total of twenty-four (24) plastic containers (12 x 8.5 x 3 inches) were used which per container contained 100 grams/1000 of 4 days old BSF larvae. The results showed that BSF larvae fed with T2-Fruit remains and T3 -Vegetable scraps yielded the highest production of 1230-1312 grams and an early maturation period of 18-19 days. Both T2-Fruit remains and T3 -Vegetable scraps have the highest nutritional value of around 43% to 47% of crude protein content, respectively as compared to the rest of the treatments. The nutritional profile of BSF larvae fed fruit and vegetable waste suggests that it may be used as a less expensive and more sustainable source of protein for pigs and poultry.